Internet connectivity disruption in Bangladesh (Bangladesh) - Voidly (Voidly Global Censorship Index, 2026)
CRITICAL severity mixed detected in Bangladesh. Data sourced from IODA, CensoredPlanet.
Censorship Incident ID: BD-2026-0068. Severity: critical. Confidence: 65%